2001
DOI: 10.1038/414901a
|View full text |Cite
|
Sign up to set email alerts
|

The genetic architecture of divergence between threespine stickleback species

Abstract: The genetic and molecular basis of morphological evolution is poorly understood, particularly in vertebrates. Genetic studies of the differences between naturally occurring vertebrate species have been limited by the expense and difficulty of raising large numbers of animals and the absence of molecular linkage maps for all but a handful of laboratory and domesticated animals. We have developed a genome-wide linkage map for the threespine stickleback (Gasterosteus aculeatus), an extensively studied teleost fis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
515
3
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 443 publications
(532 citation statements)
references
References 27 publications
(29 reference statements)
13
515
3
1
Order By: Relevance
“…Nonetheless, several studies have been carried out in stickleback, which link markers to morphological traits that differ between the stream-lake sticklebacks. For example, in a cross between benthic and limnetic sticklebacks, Peichel et al [41] mapped the location of QTLs influencing length of the pelvic spines (marker: Chr8 17.7 Mb) and first dorsal spine (marker: Chr1 18.9 Mb; Chr2 20.2 Mb). Although stream -lake fish in the current study differ in dorsal and pelvic spine lengths, none of the outlier regions we identified map near the previously described QTLs.…”
Section: Discussion (A)mentioning
confidence: 99%
“…Nonetheless, several studies have been carried out in stickleback, which link markers to morphological traits that differ between the stream-lake sticklebacks. For example, in a cross between benthic and limnetic sticklebacks, Peichel et al [41] mapped the location of QTLs influencing length of the pelvic spines (marker: Chr8 17.7 Mb) and first dorsal spine (marker: Chr1 18.9 Mb; Chr2 20.2 Mb). Although stream -lake fish in the current study differ in dorsal and pelvic spine lengths, none of the outlier regions we identified map near the previously described QTLs.…”
Section: Discussion (A)mentioning
confidence: 99%
“…Rapid degeneration of recently formed Y chromosomes has been demonstrated in Drosophila (Bachtrog et al, 2008) and sticklebacks (Peichel et al, 2001). However, there are few empirical data for W chromosomes.…”
Section: Evolution Of Sex Chromosomes In Congeneric Speciesmentioning
confidence: 99%
“…3 Schema of thyroid hormone signaling pathways in anadromous and resident forms of three-spined sticklebacks genome size, and generation time are smaller than those of salmonids. QTL mapping of several morphological and behavioral traits has been successfully performed for G. aculeatus (Peichel et al 2001;Colosimo et al 2004Colosimo et al , 2005Cresko et al 2004;Shapiro et al 2004;Albert et al 2008;Kitano et al 2009;Greenwood et al 2011). …”
Section: The Future Of Physiological Genomics Of Fish Migrationmentioning
confidence: 99%